Cancer stem cells—clinical relevance - Jones, Richard J. (2009)
Therapeutic advances over the past three decades now allow most cancer patients to achieve major clinical responses. Although clinical responses can clearly decrease side effects and improve quality of life, most cancer patients still eventually relapse and die of their disease. Many cancers have now been shown to harbor cells that are phenotypically and biologically similar to normal cells with self-renewal capacity; these so-called cancer stem cells (CSC) typically constitute only a small fraction of the total tumor burden, but theoretically harbor all the self-renewal capacity. Moreover, the CSC appears to be relatively resistant to standard anticancer therapies by co-opting normal stem cells’ intrinsic defense mechanisms, such as quiescence, efflux pumps, and detoxifying enzymes. However, the clinical importance of CSC, if any, remains unproven. Nevertheless, emerging evidence suggests that initial responses in cancer represent therapeutic effectiveness against the bulk cancer cells, while the rare CSC is responsible for relapse. Better understanding of the biology of CSC, as well as reexamining both our preclinical and clinical drug development paradigms to include the CSC concept, has the potential to revolutionize the treatment of many cancers.